Pengaruh Kepuasan Kerja, Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Moderating - Lopia Simatupang, Rebecca Kristiana; Moeljono, Moeljono (IJMA (Indonesian Journal of Management and Accounting), 2023)
The study aims to empirically examine the effect of job satisfaction, work environment, and compensation on employee performance with motivation as a moderating variable with a study on Centro Production. The population is employees who work at Centro Production. The sample in this study was 62 respondents. This research uses quantitative analysis and techniques for sampling, namely using saturated sampling techniques (census). Data collection methods through questionnaires, observation and data analysis using SPSS 25 which includes validity, reliability, classical assumption tests, multiple regression analysis, hypothesis testing using the t test, f test and R2 test and moderation test.The results showed that the independent variables of job satisfaction, work environment and motivation had a positive and significant effect on employee performance partially or stimulant. The moderation variable of motivation shows that motivation is able to moderate employee performance, but motivation cannot moderate the effect of work environment and compensation on employee performance. The coefficient of determination of 51% indicates the ability of the independent variable to predict only 51%, there are still 49% explained by variables outside the model. But through the coefficient of determination after moderated regression analysis the calculation results are 97%. So it can be concluded that after the moderation variable, the motivation variable can strengthen the influence of job satisfaction, work environment and compensation variables on employee performance.